STUDYING THE EFFECT OF TRANSPORT LAYERS ON ZrS2/MEH-PPV SOLAR CELLS: USING SCAPS -1D SOFTWARE - Mousa, Marwan S.; Al-Dmour, Hmoud; Jaradat, Emad K.; Al-Madanat, Osama Y.; Jaber, Ahmad M. D. (Assa'd); Zaidi, Beddiaf; Alali, Ahmet Sait; Aravindan, V (V N KARAZIN KHARKIV NATL UNIV, 2024)
This study investigates the effect of charge transport layers on the efficiency of Poly[2-methoxy-5-(2-ethylhexyloxy)-1,4phenylenevinylene] (MEH_PPV) and Zirconium Disulfide (ZrS2) solar cells using Scaps-1D software. It was found that by increasing the MEH-PPV thickness and decreasing its acceptor doping concentration, the efficiency (mu%), fill factor (FF), and short-circuit current density (Jsc ) decreased. Conversely, increasing the thickness of the ZrS2 electron transport layer and decreasing its donor doping density enhanced the efficiency (mu%) and short-circuit current density (Jsc) while maintaining a constant open-circuit voltage (Voc). These results can be attributed to decreased charge separation and collection in MEH-PPV and reduced optical path length in ZrS2. On the other hand, the back contact with work function is below 4.65 eV, the MEH-PPV/ZrS2 solar cells produced the lowest efficiency compared to different types of back contact. Under optimal conditions, MEH-PPV/ZrS2 solar cell shows a high efficiency of 21% when the dopant concentration of MEH-PPV and the value of the neutral defect density at the ZrS2/ MEH-PPV interface are 1022 cm(-3) and 109 cm(-3) respectively.
Keywords: SCAPS simulation; Solar cells; Doping density; Interface Defect; Work function; Physics